Atg38-Atg8 interaction in fission yeast establishes a positive feedback loop to promote autophagy. Issue 11 (1st November 2020) - Yu, Zhong-Qiu; Sun, Ling-Ling; Jiang, Zhao-Di; Liu, Xiao-Man; Zhao, Dan; Wang, Hai-Tao; He, Wan-Zhong; Dong, Meng-Qiu; Du, Li-Lin
ABSTRACT: Macroautophagy (autophagy) is driven by the coordinated actions of core autophagy-related (Atg) proteins. Atg8, the core Atg protein generally considered acting most downstream, has recently been shown to interact with other core Atg proteins via their Atg8-family-interacting motifs (AIMs). However, the extent, functional consequence, and evolutionary conservation of such interactions remain inadequately understood. Here, we show that, in the fission yeast Schizosaccharomyces pombe, Atg38, a subunit of the phosphatidylinositol 3-kinase (PtdIns3K) complex I, interacts with Atg8 via an AIM, which is highly conserved in Atg38 proteins of fission yeast species, but not conserved in Atg38 proteins of other species. This interaction recruits Atg38 to Atg8 on the phagophore assembly site (PAS) and consequently enhances PAS accumulation of the PtdIns3K complex I and Atg proteins acting downstream of the PtdIns3K complex I, including Atg8. The disruption of the Atg38-Atg8 interaction leads to the reduction of autophagosome size and autophagic flux. Remarkably, the loss of this interaction can be compensated by an artificial Atg14-Atg8 interaction. Our findings demonstrate that the Atg38-Atg8 interaction in fission yeast establishes a positive feedback loop between Atg8 and the PtdIns3K complex I to promote efficient autophagosome formation, underscore the prevalence and diversity of AIM-mediated connections within the autophagic machinery, and reveal unforeseen flexibility of such connections. Abbreviations : AIM: Atg8-family-interacting motif; AP-MS: affinity purification coupled with mass spectrometry; Atg: autophagy-related; FLIP: fluorescence loss in photobleaching; PAS: phagophore assembly site; PB: piggyBac ; PE: phosphatidylethanolamine; PtdIns3K: phosphatidylinositol 3-kinase; PtdIns3P: phosphatidylinositol 3-phosphate.